(untitled) - Majercakova, Margita (Doprava a spoje, 2007)
This paper is oriented for analyse of relations and competences among institutions Ministry of transport, posts and telecommunications of the Slovak Republic, Telecommunication Office of the SR and institutions which with office are cooperating: Antimonopoly Office of the SR and Council for Broadcasting and Retransmission. This article presents situation on the electronic communications market but also options of elimination determined defaults.